Eficiencia de la intervención de la unidad de mezclas oncológicas en el servicio de oncología y hematología del Hospital IV Víctor Lazarte Echegaray - Trujillo marzo - diciembre 2009 - García Vega, Lucía Victoria (2010)
In the field of health has become a concern emphasis to ensure that resources are allocated efficiently, but whereas in developed countries have conducted studies to the knowledge and control over medical care costs in countries like ours identification and containment of the cost of producing services are poorly studied aspects. For this reason is that in the present study, the main objective was to evaluate the efficiency of the Intervention Unit in Mixtures Cancer Oncology and Hematology IV "Víctor Lazarte Echegaray" in 2009 on grounds of Net Savings, Cost Benefit and Cost Impact, because as we know the UMO is a complementary strategy for maximizing the benefits obtained by the SDMDU in the hospital. The present work of investigation is a descriptive, cross-sectional and retrospective study, for which analyzed the consumption of anticancer drugs served by the Hospital Pharmacy and returns of these products generated by the UMO during the study period, these data was extracted from the Database Management System Hospital Pharmacy Hospital IV "Víctor Lazarte Echegaray. The number of anticancer drugs returned by the UMO to the Hospital Pharmacy for the period March to December 2009 was 10.38% and 4.26% return of medicines in both units and soles respectively, the total value served. The antineoplastic generated greater return was the Fluorouracil 250mg units with 283 units, while Trastuzumab 440mg. that gender was the largest savings soles S / 98 810.30. To evaluate the efficiency of UMO were measured indicators, obtaining that the Unit generated net savings of S/54 619.58 a Cost Impact was S/.13.35 and Cost-Benefit of 2.16, which clearly show which Cancer Mixing Unit is efficient because it results in significant savings over time for the Hospital